BELENGGU TUJUH ROH JAHAT PESAN PASTORAL YESUS DALAM MATIUS 12:43-45 - David Rade Manat Simanjuntak; Ryanto Adilang; Tesalonika Mandey (Institut Agama Kristen Negeri Manado, 2021)
Humans have a unique system called character. Character is a pattern that distinguishes attitudes and traits from one human to another. This character then becomes a non-standard measuring tool, to determine whether someone can be called good or bad. Besides face, character is the identity of a human being. However, it turns out that changes in a person's character can be influenced by many factors, both internal and external. One of the factors to be discussed is the intervention of evil spirits. Jesus explained in his sermon that evil spirits can make a person's condition worse. Even when the evil spirit is gone, he will come back inviting seven other, more evil spirits to come and destroy again. however, the second damage has a very high level of destructiveness. This study uses a qualitative method with a descriptive approach. Because it involves Bible verses, specifically the New Testament, a hermeneutic method is needed. The hermeneutic method chosen is a combination of the methods of narrative criticism and historical criticism. This research will explore narrative elements and historical facts and then combine them in an analysis to obtain substantial meaning. The results of this study are expected to provide new contributions in the field of Theology, especially Pastoral and Biblical New Testament. It is hoped that there will be a substantial understanding of evil spirits and their effects on humans